2014
DOI: 10.1021/cg500481u
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Thermotropic Phase Behavior of a Homologous Series of N-Acylglycines: Neuroactive and Antinociceptive Constituents of Biomembranes

Abstract: N-Acylglycines (NAGs) with different acyl chains have been found in the mammalian brain and other tissues. They exhibit significant biological and pharmacological properties and appear to play important roles in communication and signaling pathways within and between cells. In view of this, a homologous series of NAGs have been synthesized and characterized in the present study. Differential scanning calorimetric (DSC) studies show that the transition enthalpies and entropies of dry as well as hydrated NAGs ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 49 publications
2
29
0
Order By: Relevance
“…In the case of N-acylglycines, the incremental increase in dspacing per additional CH 2 group in the acyl chain was obtained from PXRD studies as 2.645Å, which suggested that the acyl chains in them should be perpendicular to the plane of the bilayer [43]. Consistent with this, single-crystal X-ray diffraction studies on N-myristoylglycine and N-palmitoylglycine showed that the alltrans acyl chains in them have tilt angles of 0.03 • and 0.84 • , respectively, with respect to the bilayer normal, which are negligible when compared with the tilt angle estimated for the NAAs from PXRD measurements.…”
Section: Powder X-ray Diffractionmentioning
confidence: 99%
“…In the case of N-acylglycines, the incremental increase in dspacing per additional CH 2 group in the acyl chain was obtained from PXRD studies as 2.645Å, which suggested that the acyl chains in them should be perpendicular to the plane of the bilayer [43]. Consistent with this, single-crystal X-ray diffraction studies on N-myristoylglycine and N-palmitoylglycine showed that the alltrans acyl chains in them have tilt angles of 0.03 • and 0.84 • , respectively, with respect to the bilayer normal, which are negligible when compared with the tilt angle estimated for the NAAs from PXRD measurements.…”
Section: Powder X-ray Diffractionmentioning
confidence: 99%
“…Chloride ions and water molecules form a hydrogen-bonded anionic zigzag chain core along the a crystal axis. This feature of MR is in contrast to neutral amides, including the long-chain alkyl derivatives, which are typical coformers of the N-HÁ Á ÁO C hydrogen-bonded supramolecular synthons in onedimensional chain aggregates (Ramakrishnan & Swamy, 1999;Reddy et al, 2014;Masuda et al, 2005;Dastidar, 2008;Bastiat & Leroux, 2009). 2).…”
Section: Resultsmentioning
confidence: 99%
“…In previous work, we have synthesized and characterized the self assembly, supramolecular organization and thermotropic phase behavior of N -acylalanines and N -acylglycines. 7,13 While N -acylation of glycine and alanine yields anionic amphiphiles, esterification of these amino acids with long chain alcohols would give cationic amphiphiles which may find use in developing catanionic lipid based drug delivery systems. Therefore, we have also synthesized a homologous series of L-alanine alkyl esters and characterized them with respect to aggregation properties in aqueous dispersion, 3-dimensional structure as well as interaction with sodium dodecyl sulfate.…”
Section: Resultsmentioning
confidence: 99%
“…The product obtained was recrystallized from dichloromethane at −20 • C. Overall yields of different NAAEs ranged around 80-90%. The final product thus obtained was filtered and dried by vacuum desiccation, and characterized by FTIR, 1 H-NMR, 13 C-NMR and HRMS.…”
Section: Synthesis Of N-acyl-l-alanine Estersmentioning
confidence: 99%
See 1 more Smart Citation